Knowledge, attitudes, and practices about COVID-19 pandemic: a bibliometric analysis - Laia Selva-Pareja; Laia Selva-Pareja; Carla Camí; Judith Roca; Judith Roca; Judith Roca; Anna Espart; Anna Espart; Anna Espart; Anna Espart; Carme Campoy; Carme Campoy; et al. (Frontiers Media S.A., 2023)
BackgroundIn order to avoid high rates of COVID-19 infection, one of the main tasks that must be performed is to improve the knowledge, attitudes, and practices (KAP) about the virus. In this sense, Health Education is an essential tool for dealing with the virus. The aim of health education is to educate individuals through educational, motivational, skill development, and awareness techniques, and an understanding of the main needs of KAP is essential for this. Many KAP studies were published during the COVID-19 pandemic, and the aim of the present study was to analyze these publications through a bibliometric study.MethodsA bibliometric analysis of the publications on KAP and COVID-19 was conducted in the Web of Science Core Collection database. The RStudio Bibliometrix and VOSviewer packages were utilized to analyze the scientific production, authors, citations, countries, publishers, journals, research areas, and keywords.ResultsOf the 1,129 articles published, 777 were included in the study. The year with the most publications and citations was 2021. Three authors were underlined (all from Ethiopia), due to the number of articles published, the number of citations, and the collaboration networks established. As for the countries, most of the publications came from Saudi Arabia, while China obtained the most citations. PLOS One and Frontiers in Public Health published the most articles on the subject. The most frequent keywords were knowledge, attitudes, practices, and COVID-19. At the same time, others were identified based on the population group analyzed.ConclusionThis is the first bibliometric study on KAP and COVID-19. The significant number of publications identified on KAP and its relationship to the COVID-19 pandemic, in the span of only 3 years, indicates the increased interest in this area. The study provides relevant information to researchers who are approaching this subject for the first time. It is a useful tool that can stimulate new studies and collaborations between researchers from different countries, areas and approaches. At the methodological level, a step-by-step guide is provided for future authors who wish to perform a bibliometric analysis.